(untitled) (Modern education and development, 2024)
This article explores the social and psychological characteristics of the speaker in the context of silence in oral speech. Silence, as a communicative tool, plays a significant role in conveying meaning and influencing interaction between speakers and listeners. The article investigates how the speaker’s social identity, psychological state, and the context of the conversation contribute to the use of silence. The study emphasizes the multifaceted role of silence, not just as a lack of speech, but as an active component in communication. Methods for analyzing silence in spoken interactions are discussed, followed by an evaluation of its implications in real-life speech settings.